Femoropatellar Joint Reaction Detected During a 4486 KM Ultramarathon with Mobile MRI - Schütz, Uwe Hans-Werner; Brix, Martin; Kiess, Antje; Goed, Sabine; Friedrich, Klaus; Weber, Michael; Messner, Alina; Billich, Christian; Trattnig, Siegfried (International Journal of Sports Medicine, 2020)
Almost nothing is known about the condition of the knee joints of multistage ultra-marathon (MSUM) runner. This is first image-based investigation of the femoropatellar joint (FPJ) using a mobile 1.5T MRI accompanying the MSUM TransEurope Foot-Race (TEFR) 64 stages over 4486 km. Twenty-two (20 male) subjects got a knee MRI-protocol at defined measurement intervals during TEFR: T2*-mapping (FLASH T2*-GRE), TIRM, and fat saturated PD -sequence. In the FPJ 12 different regions were evaluated regarding cartilage T2* and thickness changes and cartilage lesions in course of TEFR and a test on possible compounding factors (running burden, BMI, age) was done if being appropriate. No significant changes in cartilage thickness- and T2*-values were found during TEFR. In 8 runners, at least one single cartilage lesion (Grade 2–3) was found at baseline, but no significant race-related adjacent T2*-changes or progress of the defects could be detected. Analyses on compounding factors were negative. In knees with MPP (5) significantly lower adjacent T2*-values were found. The extreme running burden of a MSUM seems not to have a relevant negative influence on the FPJ tissues, even if cartilage lesions are present.
Keywords: cartilage; MRI; knee; marathon; running; patella